2004
DOI: 10.1007/s00595-003-2694-0
|View full text |Cite
|
Sign up to set email alerts
|

Shaggy Aorta Syndrome After Acute Arterial Macroembolism: Report of a Case

Abstract: We report the case of a patient who underwent treatment for a macroembolism in the right lower leg, which led to shaggy aorta syndrome. Anticoagulant therapy for the macroembolism and intra-aortic catheterization exacerbated the patient's renal function and triggered another massive microembolization of the visceral arteries, with a fatal outcome. To minimize the incremental complications inherent to this syndrome, awareness and prompt diagnosis with enhanced computed tomography or intravenous digital subtract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 5 publications
0
7
0
2
Order By: Relevance
“…Although the term "shaggy aorta" refers to an irregularly shaped and spiculated aorta, which is determined by visual characteristics on computed tomography (CT) angiography, an agreed definition of the condition does not yet exist. 1,2 Shaggy aorta is related to early adverse events following open surgical repair (OSR) and endovascular aneurysm repair (EVAR) for abdominal aortic aneurysm (AAA). 3,4 Peripheral and visceral embolization from a diffusely atherosclerotic aorta has been called shaggy aorta syndrome.…”
Section: Introductionmentioning
confidence: 99%
“…Although the term "shaggy aorta" refers to an irregularly shaped and spiculated aorta, which is determined by visual characteristics on computed tomography (CT) angiography, an agreed definition of the condition does not yet exist. 1,2 Shaggy aorta is related to early adverse events following open surgical repair (OSR) and endovascular aneurysm repair (EVAR) for abdominal aortic aneurysm (AAA). 3,4 Peripheral and visceral embolization from a diffusely atherosclerotic aorta has been called shaggy aorta syndrome.…”
Section: Introductionmentioning
confidence: 99%
“…4,5 We observed that the aortic morphology may also prove to be a powerful determinant of this complication and that its incidence was higher in patients with atheromatous laden aortic lumen. Both peripheral 6 and visceral 7,8 spontaneous embolisation has been described in patients with diffuse aortic atherosclerotic disease, and has been termed "shaggy aorta syndrome". The aim of this study was to evaluate the factors associated with mesenteric embolisation in patients treated with fenestrated aortic endografts.…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, for macroembolism, anticoagulants may enhance the embolic process by disrupting atheromatic plaques and must be discontinued. 12 We planned to treat our patient with surgery followed by thrombolysis and possible anticoagulation medication. The patient did not take any medication before the planned surgery.…”
Section: Discussionmentioning
confidence: 99%